(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
The Chinese Silk Road is the Trans-Eurasian network of trade routes connecting East and Southeast Asia to Central Asia, India, Southwest Asia, Mediterranean, and Northern Europe. The Road flourished roughly from 100 BC to around 1450.The Road is a system of caravan roads that in Ancient Times and Middle Ages traversed Eurasia from Mediterranean to China. From historic times it flourished the development of trade and cultural relations between peoples and actors involved. The Silk Road acts as a symbol of openness, inclusiveness, cooperation and peace. It also acts as a place where the humanist, spiritual, cultural, artistic and technical exchanges take place. The One Belt and One Road program is a major strategic measures introduced by China in response to the emerging trends in Economic Globalization. China proposes a new approach of promoting worldwide economic prosperity and to benefiting other regions in terms of driving forward cross-regional economic integration through economic growth in China and Asia. In the Post Cold War Period, there are at least two reconstruction that are historically very significant in Eurasian continent, one is the implosion of Soviet Union, the other will be the “Belt and Road” initiative in China. In this context the present study wants to explore the new project of Silk Route, challenges and prospects that china is facing in building its project. It is thus significant in analyzing the impact of the project to reconstruct regional interests and balance powers throughout the world especially Central Asia. The study will also focus on the following questions as what are the future prospects, will the neighbouring countries benefit from the initiative? And will China‟s investment enrich the world?